Comparison of Deflazacort and Prednisone in Duchenne Muscular Dystrophy - KARIMZADEH, Parvaneh; GHAZAVI, Ahad (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Karimzadeh P, Ghazavi A. Comparison of Deflazacort and Prednisone in Duchenne Muscular Dystrophy. IranianJournal of Child Neurology 2012;6(1):5-12. Objective Duchenne muscular dystrophy (DMD) is a degenerative disease that usually becomes clinically detectable in childhood as progressive proximal weakness. No cure is yet available for DMD, but the use of steroids improves muscle strength and function. This study has been carried out to select the best steroid for the management of DMD. Materials & Methods This study is a single-blind, randomized clinical trial with a sample volume of 34 DMD patients. Half of these patients were treated with deflazacort (0.9 mg/kg daily) and the other half with prednisone (0.75 mg/kg daily) for a period of 18 months. The motor function score and excess body weight were registered one year after the start and also at the end of the study and compared between the two groups. Results Deflazacort was more effective in the improvement of motor function after one year, but there was no significant difference between the two drugs at the end of the study (18 months after start). Weight gain after one year and at the end of the study was higher in prednisone group and steroid treatment with deflazacort appears to cause fewer side effects than prednisone regarding weight gain. Conclusion Deflazacort seems to be more effective than prednisone in the improvement of motor function causing fewer side effects, particularly weight gain. This medication may be important for the improvement of motor function and could be used as the best steroidal treatment for Duchenne muscular dystrophy. References Lankester BJA, Whitehouse MR, Gargan MF. Duchenne muscular dystrophy. Current Orthopedics 2007;21:298- 300. Wenger DR, Rang M. The art and practice of children’s orthopedics. Philadelphia, PA: Lippincott; Baltimore: Williams and Wilkins; 1993. Sussman M. Duchenne muscular dystrophy. J Am Acad Orthop Surg 2002 Mar-Apr;10(2):138-51. Escolar DM, Leshner RT. Muscular dystrophies. In: Swaiman KF, Ashwal S, Ferriero DM. Pediatric Neurology. 4th ed. Philadelphia: Mosby; 2006. p. 1967-86. Sarnat HB, Menkes JH. Disease of the motor unit. In: Menkes JH, Sarnat HB, editors. Child Neurology. 7th ed. Philadelphia: Lippincott Williams & Wilkins; 2005. p. 984-9. Biggar WD, Politano L, Harris VA, Passamano L, Vajsar J, Alman B, et al. Deflazacort in duchenne muscular dystrophy: a comparison of two different protocols. Neuromuscul disord 2004 Sep;14(8-9):476-82. Radley HG, De Luca A, Lynch GS, Grounds MD. Duchenne muscular dystrophy: focus on pharmaceutical and nutritional interventions. Int J Biochem Cell Biol 2007;39(3):469-77. Biggar WD, Klamut HJ, Demacio PC, Stevens DJ. Duchenne muscular dystrophy: current knowledge, treatment and future prospects. Clin Orthop Relat Res 2002 Aug;401:88-106. Sohn RL, Gussoni E. Stem cell therapy for muscular dystrophy. Expert Opin Biol Ther 2004 Jan;4(1):1-9. Houde S, Filiatrault M, Fournier A, Dube J, D’Arcy S, Berube D et al. Deflazacort use in duchenne muscular dystrophy: an 8-year follow-up. Pediatr Neurol 2008 Mar;38(3):200-6. Bonifati MD, Ruzza G, Bonometto P, Berardinelli A, Gorni K, Orcesi K et al. A multicenter double-bind randomized trial of deflazacort versus prednisone in Duchenne muscular dystrophy: analysis after 2 years. Basic Appl Myol 2000;10:171-5. Reitter B. Deflazacort vs. prednisone in Duchenne muscular dystrophy: trends of an ongoing study. Brain Dev 1995;17 Suppl:39-43. Polgar G, Promadhat V. Standard values. In: pulmonary function testing in children: techniques and standards. Philadelphia: W.B. Saunders, 1971:102-3. Biggar WD, Gingras M, Febling DL, Harris VA, Steele CA. Deflazacort treatment of Duchenne muscular dystrophy. J Pediatr 2001 Jan;138(1):45-50.